A Digital Nudge to Counter Confirmation Bias - Thornhill, Calum; Meeus, Quentin; Peperkamp, Jeroen; Berendt, Bettina (Frontiers in Big Data, 2019)
Fake news is an increasing issue on social media platforms. In this work, rather than detect misinformation, we propose the use of nudges to help steer internet users into fact checking the news they read online. We discuss two types of nudging strategies, by presentation and by information. We present the tool BalancedView, a proof-of-concept that shows news stories relevant to a tweet. The method presents the user with a selection of articles from a range of reputable news sources providing alternative opinions from the whole political spectrum, with these alternative articles identified as matching the original one by a combination of natural language processing and search. The results of an initial user study of BalancedView show that nudging by information may change the behaviour of users towards that of informed news readers.